O narrador demoníaco de Lagoa Branca na obra Os tambores silenciosos, de Josué Guimarães - Marins, Loreci Alves (2021)
This dissertation intends to interpret the work Os tambores silenciosos, by Josué Guimarães, in relation to the construction of meanings regarding the narratological statutes and their interpretative constituents. Realism, as aesthetics, associated with the wide variety of artistic productions, is also based on the formation of the novel as a genre, which can be considered a watershed in relation to previous literary production. Os tambores silenciosos, by Josué Guimarães, is a recent example of the trends of representation inaugurated by Defoe's fiction. According to Ian Watt, there is the use of non-traditional plots, either entirely invented, or partially based on an incident associated with the political demands of modernity, which resort in contemporary times, that is, to the attempts to impose autocratic and authoritarian political orders, led by nationalist and fascist-based authorities. Thus, this research, focusing on the romantic genre, will associate two characteristic elements to the narrative, sometimes in the order of the narrator, sometimes in the field of the character studies. As a diegesis, the narrative that focuses on the hero's individual trajectory, on his demonic psychology, according to György Lukács. In this research, the character's condition, dissociated and in search, is transmigrated to the function of narrating, characteristic and complex with regard to the novel. Furthermore, it is necessary to consider the ways of understanding the novel postulated by Jean Pouillon, in the work O tempo no romance, which proposes the formal distinction of two visions: “behind” and “with”, from the perspective of the Pilar sisters, who the reader follows in the narrative. In this way, it is necessary to understand the voice that narrates and seeks something in the flights of this perspective that tries to unveil life and seeks some reorganization in the degradation of the world based on Todorov regarding Pouillon's visions. For this, the perspective of Gérard Genette complements the study of the narrator, it is about focusing. Added to this, genetic criticism is fundamental, once its object of study is the manuscript as the bearer of the creation process, according to Philippe Willemart, Claudia Amigo Pino, Roberto Zular, since this look of the characters is part of the manuscript of a map of Lagoa Branca made by Josué Guimarães. In the image, in a way, an allegorical form is constituted as part of what will be the whole, a Lagoa Branca space, surrounded but invaded, either by demonic black birds, or by the eyes of the narrator. Therefore, as Louis Hay says, the observation of a drawing in the manuscript is a kind of return to the sources.